MANAJEMEN PROGRAM PEMBINAAN SANTRI MELALUI METODE POLA DAKWAH DI PESANTREN MODERN: id - Asep Abdul Aziz; Nurti Budiyanti; Andewi Suhartini; Nurwadjah Ahmad (STIT PRINGSEWU, 2021)
The character of Islam needs to be nurtured early on in overcoming increasingly degrading moral degradation. One of the educational institutions that has a big role in fostering character is pesantren. Pesantren Kreatif IHAQI Boarding School Bandung is one of the pesantren educational institutions present in the era of industrial revolution 4.0 that applies da'wah pattern method in the learning process. This research uses qualitative approach with case study method at IHAQI Boarding School Bandung Creative Boarding School. The results of the study illustrate that this pesantren has a typical management of learning methods, namely applying da'wah pattern methods in the learning process. At the planning stage, this method is considered to have been planned carefully, it is seen by the implementation stage that is constructed and systematic. As for the implementation stage, this method is considered to have been carried out effectively. However, in the covid-19 situation, implementation becomes hampered so that cooperation between educators and learners in developing this method of da'wah pattern becomes reduced. Meanwhile, the evaluation of the use of da'wah pattern method in learning in IHAQI Boarding School Creative Boarding School is enough to give a very deep impression to all learners to bequeath Islamic values. So that all learners are able to increase their potential, both related to cognitive, affective, psychomotor and spiritual aspects. These aspects are very important to note the development through process evaluation and evaluation of results carried out by educators in the learning process. Thus good management will have an impact on achieving learning objectives.